Physical properties and in vitro transfection efficiency of gene delivery vectors based on complexes of DNA with synthetic polycations - Reschel, Tomás; Konák, Cestmír; Oupický, David; Seymour, Leonard W; Ulbrich, Karel (Journal of controlled release, 2002)
Biophysical properties of polycation/DNA complexes designed for gene delivery were studied with respect to the conditions of their preparation, chemical structure and molecular weight of the polycations involved. The polycations used included a variety of cationic polymers and copolymers containing primary and tertiary amino or quaternary ammonium groups. It was found that the molecular weight and the size of these polyelectrolyte complexes (PECs) increase with increasing temperature and pH of the buffer. By decreasing the molecular weight of polycations used for PEC formation, the complexes become unstable towards coagulation in aqueous solution at lower pH. The self-assembly of DNA with low-molecular-weight polycations in water provides PECs with the lowest molecular weight, smallest size and the lowest density but their stability in NaCl solutions is very poor. Despite the complexity of the multistep transfection process, a direct correlation between the transfection efficiency in vitro and the stability of the complexes in NaCl solutions and coagulation in 0.15 M NaCl solution was found. DNA complexes with polycations containing primary amino groups showed the best stability in saline solutions and also the best transfection activity. PECs formed by polycations with quaternary ammonium groups were the least resistant to destruction by the added salt and provided the lowest activity in transfection assays. The highest transfection activity was found for DNA complexes formed with a statistical copolymer containing primary and tertiary amines.
Keywords: molekulová hmotnost; polyelektrolyty; roztoky; transfekce; Scattering, Radiation; Molecular Weight; Sodium Chloride; Transfection; Genetic Vectors; chemické jevy; Escherichia coli; Chemical Phenomena; Drug Stability; Microscopy, Atomic Force; chlorid sodný; melanom experimentální; světlo; mikroskopie atomárních sil; polyaminy; Drug Delivery Systems; Chemistry, Physical; Animals; Solutions; stabilita léku; fyzikální chemie; zvířata; radiační rozptyl; nádorové buňky kultivované; myši; DNA; Polyelectrolytes; genetické vektory; Tumor Cells, Cultured; Polyamines; Light; Mice; lékové transportní systémy; Melanoma, Experimental